Asuhan Kebidanan Komprehensif pada Ny. S di Rumah Sakit Ibu dan Anak Masyita - Suling, Fakhira; Abeng, Andi Tendri; masnilawati, andi (Window of Midwifery Journal, 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) remain major health issues in Indonesia. Pregnancy, childbirth, postpartum, newborn care, and family planning services are physiological periods with high risks for maternal and infant morbidity and mortality. One strategic effort to reduce MMR and IMR is to provide comprehensive and continuous midwifery care through the Continuity of Care (CoC) approach. This final project aims to implement comprehensive midwifery care for Mrs. S at RSIA Masyita Makassar, covering antenatal care, intranatal care, newborn care, postpartum care, and the selection of contraceptive methods. The care was provided using the 7-step Varney midwifery management framework and documented using the SOAP format. Data were collected through interviews, observations, physical examinations, supporting examinations, and document reviews. The results showed that Mrs. S (G3P1A1), at 36–38 weeks of gestation, attended four antenatal visits without any pregnancy danger signs. Labor progressed spontaneously, and the baby, a female, cried immediately after birth, weighed 3,160 grams, measured 50 cm in length, with a head circumference of 30 cm and chest circumference of 31 cm. The postpartum period was normal, with three follow-up visits and no complications. The patient chose progestin-only pills as her postpartum contraceptive method. Through this care, it is expected that the patient will improve her knowledge and awareness of possible complications, and this experience will also serve as a valuable opportunity for the author to enhance her skills in delivering comprehensive midwifery care